Resistance to colistin and various antibiotics in non-typhoidal Salmonella - Rumeysa Bildik; Betigül Öngen (Journal of Global Antimicrobial Resistance)
BACKGROUND: Non-typhoidal Salmonella has been reported as one of the four major global causes of diarrheal diseases by the World Health Organization. In recent years, Salmonella strains resistant to both antibiotics used in treatment and colistin have been increasing worldwide, and therefore resistance is monitored on a country-by-country basis. In this study, it was aimed to determine the minimal inhibitor concentration (MIC) values of antibiotics frequently used in the treatment and of colistin and to investigate plasmid-mediated mcr genes that play a role in colistin resistance. METHODS: MIC values for colistin (COL), ampicillin (AMP), trimethoprim-sulfamethoxazole (SXT), ciprofloxacin (CIP) and ceftriaxone (CRO) were determined by broth microdilution method in 83 Salmonella (70 S. Enteritidis, 13 S. Typhimurium) isolates from patients with gastroenteritis in accordance with the European Committee on Antimicrobial Susceptibility Testing recommendations and mcr-1 and mcr-2 genes were investigated by multiplex PCR method. RESULTS: Resistance to COL, CIP and AMP were found 13.25%, 4.81% and 1.2%, respectively. All Salmonella strains were susceptible to SXT and CRO. MIC ranges and MIC50-MIC90 values were found 0.25-8 mg/L and 1-4 mg/L for COL; 1-32 mg/L and 2-2 mg/L for AMP; 0.06-0.5 mg/L and 0.125-0.125 mg/L for SXT; 0.008-0.5 mg/L and 0.016-0.03 mg/L for CIP and 0.03-0.5 mg/L and 0.06-0.125 mg/L for CRO, respectively. The mcr-1 and mcr-2 genes were not detected in Salmonella isolates. CONCLUSIONS: High-level and multi-resistance were not observed in our isolates. While resistance was generally low, the highest resistance rate was observed against colistin.